2017
DOI: 10.1111/labr.12117
|View full text |Cite
|
Sign up to set email alerts
|

Do minimum wages increase job satisfaction? Micro‐data evidence from the new German minimum wage

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 41 publications
2
25
1
1
Order By: Relevance
“…But employers conceded that while the minimum wage triggered these actions, it was not the actual reason behind these adjustments. On the level of individual employees, quantitative studies show that employees who benefitted from the introduction of the minimum wage reported a slight increase in their subjectively perceived job satisfaction, while work effort has not increased significantly (Bossler and Broszeit 2016;Pusch and Rehm 2017). At the same time, the requirements and workload of these groups seem to have increased (Pusch and Rehm 2017;Koch et al 2018).…”
Section: Labour Productivitymentioning
confidence: 99%
“…But employers conceded that while the minimum wage triggered these actions, it was not the actual reason behind these adjustments. On the level of individual employees, quantitative studies show that employees who benefitted from the introduction of the minimum wage reported a slight increase in their subjectively perceived job satisfaction, while work effort has not increased significantly (Bossler and Broszeit 2016;Pusch and Rehm 2017). At the same time, the requirements and workload of these groups seem to have increased (Pusch and Rehm 2017;Koch et al 2018).…”
Section: Labour Productivitymentioning
confidence: 99%
“…Autor et al (2016) point out that potential mechanisms behind wage spillovers are not fully understood. Applications for Germany include Brautzsch and Schultz (2015), Amlinger et al (2016), Mindestlohnkommission (2016b), Caliendo et al (2017), Bossler and Broszeit (2017), Bruttel et al (2018), and Ahlfeldt et al (2018) who all confirm wage increases at the bottom of the distribution for Germany. Another important finding is the significant degree of non-compliance.…”
Section: Literaturementioning
confidence: 99%
“…To analyze well-being effects of the minimum wage, the SOEP has several advantages over alternative data sources that are used in the literature (e.g., Bossler and Broszeit, 2017;Pusch and Rehm, 2017): In particular, the SOEP includes different measures of well-being, including life satisfaction, job satisfaction, and pay satisfaction. It also includes small organizations instead of only focusing on large and medium enterprises (Bossler and Broszeit, 2017), which is an important aspect because small organizations tend to be more strongly affected by the minimum wage (Falck et al, 2013;Heumer et al, 2013;Kalina and Weinkopf, 2015;Pusch and Rehm, 2017). In addition, as a representative data set the SOEP does not oversample particular groups such as those who receive unemployment benefits (Pusch and Rehm, 2017).…”
Section: Datamentioning
confidence: 99%
“…Only few studies, however, have analyzed the effects of minimum wages on well-being (Bossler and Broszeit, 2017;Pusch and Rehm, 2017). 1 The present study investigates how the introduction of a minimum wage influences different dimensions of well-being: life satisfaction, job satisfaction, and pay satisfaction of those who earned less than the minimum wage before.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation